The European Scallop Fisheries for Pecten maximus, Aequipecten opercularis, Chlamys islandica, and Mimachlamys varia - Duncan, Peter F.; Brand, Andrew R; Strand, Oivind; Foucher, Eric (HAL CCSD, 2016)
The European fisheries for Pecten maximus, Aequipecten opercularis, Mimachlamys varia and Chlamys islandica are among the best-studied scallop fisheries worldwide. This chapter provides a current perspective of the scientific research related to the four species and their fisheries, covering biology, physiology, ecology, fishery statistics, management and current developments in the Isle of Man, United Kingdom, Norway, France, Spain, Iceland and Greenland.The history of these fisheries demonstrates expansion, ‘boom and bust’ and terminal decline; processes still evident today. Despite their economic importance and good underlying scientific knowledge, the fisheries are often data poor regarding stock status and are typically poorly managed, despite a large number of regulations and control measures. Significant issues remain regarding entry restrictions, effort control, stock conservation and spatial management.Scallop recruitment processes are inherently unpredictable, and the subsequent complex relationship with fisheries stock status has led to experiments with closed areas to protect high-density broodstock areas, boost reproductive output and protect settlement habitats and biodiversity. Larger scale interactions between fisheries and spatial management, both positive and negative, are likely in the near future, as the EU Habitats Directive requires the establishment of marine protected areas for habitat and biodiversity features under the Natura 2000 initiative. While this will restrict the largely open access enjoyed by scallop fishermen, closed areas, as sanctuaries for scallops, and with proven fishery benefits, are likely to be beneficial for fisheries in the longer term.The general expansion of effort and vessel capacity in European scallop fisheries, the nomadic nature of larger classes of vessel and the lack of coordinated management, particularly in the United Kingdom, has led to more locally based co-management, especially in inshore areas. This has the potential for greater resource stewardship ...